In times of a pandemic: performance of the municipalities consortium with CIDENNF in the execution of the PNAE in 2020 (Research, Society and Development, 2022)
The National School Feeding Program (PNAE) is one of the longest-running school feeding programs in history. Its recent reformulation, which took place through Federal Law 11,947/2009, brought important changes; among others, the strengthening of the approximation of Food and Nutritional Security strategies that are guided by the principles of the Human Right to Adequate Food; and the requirement that at least 30% of the resources transferred to the municipalities be used to purchase food from family farming. It is considered a virtuous link that links healthy eating to public school students with support for sustainable rural development. A research was carried out with the municipalities consortium with CIDENNF on the performance in the execution of the PNAE in the years 2019 and 2020 and possible effects caused by the Covid 19 pandemic on their execution. The objective of the research is to shed light on the topic and, who knows, to reorient strategies to strengthen the program.